2018
DOI: 10.3389/fmars.2018.00339
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Food and Temperature on North Sea Sandeels Using a New Dynamic Energy Budget Model

Abstract: The zooplanktivorous schooling fish sandeels A. marinus comprise a quarter of North Sea fish biomass and are essential food for a number of marine mammals and birds. However, in recent decades there has been a decline in the abundance of older sandeels, with increased overwinter mortality proposed as a contributor. To survive winter animals require a minimum energy reserve which is determined by temperature, prey abundance, and possibly prey size. Here a new dynamic energy budget model is created to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…They evaluated the minimum threshold of condition factor for successful reproduction as 4.5. MacDonald, Speirs, Greenstreet, and Heath () showed using a dynamic energy budget model that copepod biomass affected the growth and mortality of the North Sea sandeel Ammodytes marinus . Kuzuhara et al () revealed that food availability before estivation strongly affects various reproductive factors such as maturity rate and fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…They evaluated the minimum threshold of condition factor for successful reproduction as 4.5. MacDonald, Speirs, Greenstreet, and Heath () showed using a dynamic energy budget model that copepod biomass affected the growth and mortality of the North Sea sandeel Ammodytes marinus . Kuzuhara et al () revealed that food availability before estivation strongly affects various reproductive factors such as maturity rate and fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment has been maintained while the number of older sandeels has declined (Heath et al, 2012). Two main factors have been proposed as responsible for the decline in sandeel abundance, increases in overwinter and predation mortality of 0-group individuals (MacDonald et al, 2018). Starvation risk decreases with increasing size (van Deurs et al, 2011); therefore, 0-group length prior to overwintering may correlate with overwinter mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A significant positive effect of fish length on abundance of age-0 sandeel was found. Different mortality pathways have been proposed for first-feeding larvae (Wright and Bailey, 1996;Henriksen et al, 2018), the larval drift phase (Gurkan et al, 2012(Gurkan et al, , 2013, and overwintering of post-settled juveniles (van Deurs et al, 2011b;MacDonald et al, 2018). The size of age-0 was measured only in winter, which makes it difficult to favour any particular mechanism, but theory about early life and recruitment in fish provide insights to the processes that might be involved.…”
Section: Tablesmentioning
confidence: 99%
“…Bigger is also better for avoiding starvation of settled juveniles, since mass-specific metabolism during overwintering decrease with increasing size (van Deurs et al, 2011b). Thus, important factors affecting survival of sandeel during the first year of life are likely to be associated with changes in food condition and predation mortality (Eliasen et al, 2011;MacDonald et al, 2018MacDonald et al, , 2019. A potential close relationship with Calanus copepods has been investigated on several occasions (van Deurs et al, 2009(van Deurs et al, , 2015, where in particular "match-mismatch" (Cushing, 1990) relationships between the production of Calanus eggs and larval hatching have been highlighted (van Deurs et al, 2009;Régnier et al, 2017).…”
Section: Tablesmentioning
confidence: 99%